1984
DOI: 10.1136/bjo.68.2.79
|View full text |Cite
|
Sign up to set email alerts
|

Retinal function in high refractive error assessed electroretinographically.

Abstract: SUMMARYThe retinal function of patients with high refractive error was studied eletroretinographically. Thirty-one hypermetropic patients, 7 myopic patients, and 7 patients with either unilateral or bilateral aphakia participated in the study. The ERG responses were measured in the light-and dark-adapted states. It was found that myopic eyes were characterised by subnormal amplitude but normal pattern, expressed by normal relationship between the b-wave amplitude and the a-wave amplitude. In aphakia the ERG re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 5 publications
2
35
1
Order By: Relevance
“…2,8,9,18,19 Researchers have suggested that the reduced ERG amplitude could result from an increase in the subretinal space, 20 reduced image size, decreased retinal illumination, and the reduced retinal cell density 9,21 in the elongated eyeball. However, none of these factors could explain the findings in children.…”
Section: Discussionmentioning
confidence: 99%
“…2,8,9,18,19 Researchers have suggested that the reduced ERG amplitude could result from an increase in the subretinal space, 20 reduced image size, decreased retinal illumination, and the reduced retinal cell density 9,21 in the elongated eyeball. However, none of these factors could explain the findings in children.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased amplitudes may indicate retinal dysfunction or degeneration. However, a marked reduction in a-and b-wave amplitudes, as observed in the PTHS-patient, is also associated with high myopia (Perlman et al 1984;Yoshii et al 2002;Flitcroft et al 2005). Moreover, the implicit times measured in the ERG recordings, which are more reliable parameters in very long eyes, were within the normal range in our patient, again rather negating presence of a panretinal degenerative or dystrophic disease.…”
Section: Discussionmentioning
confidence: 54%
“…It has previously been seen that high myopia results in subnormal amplitudes of the maximal response, the rod and cone response, the light adapted oscillatory potentials and the flicker response [25], while the relationships between the a-and b-wave amplitudes remain normal [23]. The amplitudes of the S-cone and L, M-cone b-wave have also been shown to be affected in highly myopic subjects [24].…”
Section: Discussionmentioning
confidence: 92%
“…Therefore, in complete CSNB, according to an assumed dysfunction of the ON-pathway, at least slight alteration of the a-and d-waves can be expected beside severe b-wave abnormalities. At the same time, complete CSNB is usually associated with myopia, which has been shown to influence the electroretinogram (ERG) [23][24][25], although its effects on photopic ON-and OFF-responses have not been studied yet. The aim was thus to explore the ON-and OFF-responses in complete CSNB through increasing stimulus intensities, to differentiate the effects of ONpathway dysfunction from the effects of myopia.…”
Section: Introductionmentioning
confidence: 99%